2018
DOI: 10.1101/319657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aurora B is required for programmed variations of cytokinesis during morphogenesis in theC. elegansembryo

Abstract: 29While cytokinesis has been intensely studied, how it is executed during 30 development is not well understood, despite a long-standing appreciation that various 31 aspects of cytokinesis vary across cell and tissue types. To address this, we 32 investigated cytokinesis during the invariant C. elegans embryo lineage and found 33 several reproducibly altered parameters at different stages. During early divisions, 34 furrow ingression asymmetry and midbody inheritance is consistent, suggesting 35 specific regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…A few studies have started to answer this question. A study using Caenorhabditis elegans showed that MBs translocate and align at the intestinal lumen formation site ( Bai et al. , 2018 ).…”
Section: Mbs As a Polarity Cuementioning
confidence: 99%
“…A few studies have started to answer this question. A study using Caenorhabditis elegans showed that MBs translocate and align at the intestinal lumen formation site ( Bai et al. , 2018 ).…”
Section: Mbs As a Polarity Cuementioning
confidence: 99%